Leaching of Base Cations from Dairy Slurry Applied to an Agricultural Volcanic Ash Soil - Quiroz-Espinoza, M (Springer, 2019)
Studies regarding leaching in soils have focused on the main nutrients and trace metals released. There is a lack of knowledge regarding base cations’ behavior when applied to volcanic-ash soils as dairy slurry. Our objective was to study the movement of elements through a limed pasture’s soil using the in situ technique of suction lysimeters, installed at 50-cm depths. Moreover, we used soil moisture sensors to track the movement of the soil solution up to the sampling depth. Calcium and magnesium water samples showed no significant differences in concentrations between the control and fertilized treatments, while sodium concentrations were clearly higher in the fertilized plots. Calcium and sodium exports were highest in the fertilized plots. We concluded that although lime application is recommended for mitigating aluminum toxicity and high phosphorus adsorption in acidic soils, in this case, it produced high Ca2+ losses that compounded those attributable to the fertigation of dairy slurry. It also induced Na+ losses in deeper soil zones when slurry was applied at doses higher than the pasture requirements and at inadequate seasons. Therefore, adequate management practices are needed to balance the beneficial effects of liming with dairy slurry applications. © 2019, Sociedad Chilena de la Ciencia del Suelo.